ENGLISH TEXTBOOKS USED AT BANYUASIN SENIOR HIGH SCHOOLS: BASED ON CURRICULUM 2013 - Wahyudi, Agus; Mirizon, Soni; Inderawati, Rita (English Community Journal, 2018)
The purposes of this research were to find out (a) to what extent the English textbooks used by the public senior high schools in Banyuasin matched the requirements of Curriculum 2013, (b) which textbooks met the objectives of TEFL based on Curriculum 2013, (c) what were the teachers’ perceptions of the English textbooks used by the public senior high schools in Banyuasin, (d) what were general qualities found out in the textbooks. Descriptive analytics and quantitative method were used in this research The samples were 22 teachers of English who taught at public senior high schools in Banyuasin. The data were based on (1) documentation, in terms of three English textbooks, (2) three questionnaires were used, a checklist for raters, teacher's evaluation, and teacher's ideas about general qualities. The results showed that (a) those three textbooks matched the requirement of the 2013 Curriculum, (b) the highest occurrence of the Kemendikbud textbook was 4.33 (good), Bumi Aksara was 3.87 (good), Erlangga was 3.49 (adequate) based on the scale which meant the textbooks met the objectives of TEFL stated in the newest curriculum, (c) teachers’ perceptions of the SMAN English textbooks were positive based on the requirements in the questionnaire of the three textbooks they evaluated, (d) there were some general qualities found out in the textbooks. Then, those three textbooks were recommended to use in the teaching and learning process.